DAMPAK MODEL TGT BERBASIS AFIFEDU TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS PADA MATERI PENJUMLAHAN DI KELAS II SEKOLAH DASAR - Siti Jubaedah; Rayi Siti Fitriani; Ety Sukaetini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the impact of the Teams Games Tournament (TGT) model based on the Afifedu game on students' mathematical understanding ability in addition for second-grade elementary school students. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. Data were collected through pretests and posttests of mathematical understanding ability. The results showed that the mean score of the experimental class increased from 61.25 to 80.30, while the control class increased from 51.80 to 59.85. The independent samples t-test yielded a significance value of 0.001 < 0.05, indicating a significant difference between the two classes. The effect size analysis showed that the Teams Games Tournament (TGT) model based on the Afifedu game had a high effect on students' mathematical understanding ability. Therefore, the model can improve students' mathematical understanding ability in addition.